Investigating the mechanism of downslope bentonite erosion in GCL liners using X-Ray CT. Issue 1 (February 2019) - Mukunoki, T.; Sato, K.; Fukushima, J.; Shida, K.; Take, W.A.
Abstract: Exposed composite GMB-GCL liners are at risk of downslope bentonite erosion caused by the release of low ionic strength condensed water onto the top surface of the GCL following daily solar heating. This paper investigates the use of X-ray computed tomography (X-ray CT) to quantify the thinning of the bentonite layer and the application of X-ray diffraction techniques (XRD) to investigate the changes in clay chemistry (if any) of the bentonite from the virgin GCL to the eroded bentonite. The effect of specimen size and scanning orientation was investigated resulting in a revised testing procedure in which the CT scanning orientation was changed from horizontal to vertical to permit a longer test specimen which was also sealed at the bottom edge to minimise the edge boundary condition. The X-ray CT results provide highly visual evidence that a) bentonite thinning immediately under the upper cover geotextile is the initial location of erosion, and b) the bentonite core erodes at a significantly higher rate when not covered by a geotextile than when covered by a geotextile. These observations indicate that the upper geotextile of the GCL plays a significant role in controlling the rate of bentonite erosion. Finally, a comparison of the virgin and runoff bentonite properties was conducted to investigate potential changes in swell index, X-ray diffraction results, and concentration of Na and Ca cations. The runoff bentonite was observed to had a significantly higher swell index (40 ml/2 g) than the virgin bentonite (28 ml/2 g) and lower Na and Ca concentrations. This finding is consistent with the observation from XRD analyses of the runoff bentonite which illustrate that the clay fraction of the bentonite is preferentially eroded by the application of DI water.